Antimicrobial, anticancer activities and molecular docking of eco-friendly chitosan nanocapsule loaded with biosynthesized titanium nanoparticles by Aspergillus flavus - El-Gazzar, Nashwa; Rafat, Marwa; Rabie, Gamal; Sitohy, Basel (Frontiers in Microbiology, 2026)
IntroductionChitosan have been leveraged to create chitosan nanocapsules within a bio-based nanocarrier system, enhancing efficacy and overcoming widespread microbial resistance. To generate chitosan nanocapsules (CNCs) that act as inhibitory agents against pathogenic microbes, this study combined titanium nanoparticles (TiO2 NPs) with chitosan nanoparticles (Cs NPs).MethodsA.flavus was used for the biosynthesis of TiO2NPs. Dynamic light scattering (DLS), zeta potential, atomic force microscopy (AFM), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray diffraction (XRD), were utilized to assess the physicochemical properties of TiO2NPs and their CNCs. These techniques clarified particle diameter, charge stability, specific surface area, surface morphology, shape, dimensional forms, and structural parameters, respectively.ResultsThe findings showed that TiO2NPs and their nanocapsules achieved an encapsulation efficacy of over 86.7 ± 1.8% at 1.5% w/v chitosan concentration, with particle sizes of 40.7, 40.6, and 87.3 nm for TiO2NPs, CsNPs, and CNCs, respectively. Nanoparticle stability was confirmed by a zeta potential greater than –30.1 ± 4.5mV for TiO2NPs. Furthermore, TiO2NPs and their nanocapsules suppressed both Gram-positive and Gram-negative bacteria, with CNCs exhibiting more potent inhibitory effects than either TiO2NPs or CsNPs. The minimum inhibitory concentrations (MICs) of CNCs against Salmonella typhimurium and Aspergillus fumigatus were remarkably low, at 20 and 10 μg mL−1, respectively. TEM images of S. typhimurium and A. fumigatus treated with CNCs exhibited asymmetric cell deformations, wrinkled external surfaces, cell depressions, and declined cell counts. Cytotoxicity studies showed that CNCs exhibited non-cytotoxic behavior on normal human melanocytes (HFB4). In contrast, CNCs reduced the viability of human colon carcinoma (HCT-116) and hepatocellular carcinoma (HepG-2).ConclusionNanomaterials, both alone or in nanocapsules, offer a promising alternative for inhibiting harmful microorganisms and represent a potential pathway for the development of anticancer medications. The findings indicate that CNCs are safe and effective against multidrug-resistant bacteria and fungi, making them a viable alternative to current antibiotic therapies.